Prototype Design of Android Based Bus Maintenance System in PT. Sumber Jaya Trans Tangerang - Sulaeman, Yudi; Alawi, Syihabudin; Alfiah, Fifit; Salim, Turki (International Journal of Engineering and Emerging Technology; Vol 5 No 2 (2020): July - DecemberDO - 10.24843/IJEET.2020.v05.i02.p27, 2020)
Tourism transportation companies such as the Sumber Jaya Trans bus are a means used to facilitate an agency or company in conducting tourism trips. With the use of a means of transportation, maintenance is definitely needed for the continued use of the vehicle in the long term. At PT. Sumber Jaya Trans Tangerang has a problem, namely regarding the reporting of vehicle maintenance data that still uses the web, mechanics who have repaired bus vehicles fill out maintenance reports on a web so that it takes a very long time. With the existing problems, the authors propose an Android-based bus maintenance system. Using the PIECES analysis method. The system design uses object-oriented analysis method with Unified Modeling Language (UML), programming language for Web Service using PHP with Laravel framework, programming language for Android using Dart with Flutter framework. Android was chosen because of its popularity among Indonesians as a mobile operating system capable of replacing computer jobs. Therefore we need an Android-based system that can assist in reporting vehicle maintenance data to make it more effective and efficient.